PLA Improvement Using Nanocomposite and Plasma Modification - Rattanarojanakul, Nikom; Nuangnun, Chote; Aunsaart, Wichaladda; Tirawoot, Tanapat; Srikhongrak, Somyos (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 1 (2023): January - March 2023, 2022)
This work studied the effects of Oxygen (O 2 ), Nitrogen (N 2 ) and Air plasmas on the surface modification of Polylactic acid (PLA) films. PLA films with 0.01 mm thickness were prepared from pure PLA material, while the PLA nanocomposite was prepared by mixing pure PLA with 5.00 wt.% of Organoclay (Cloisit ® 30B). The plasma discharge was operated by -800 V DC of applied voltage at 0.1 mbar. The samples were placed on the substrate inside the plasma reactor and exposed to the plasma gases for 10, 15 and 20 min. The results showed that the hydrophobic property of pure PLA film can be increased by O 2 exposure for 10 min and air plasma exposure for 20 min. Whilst the hydrophilic properties of PLA nanocomposite film were elevated when exposed for 20 min to the air and N 2 plasma. In addition, PLA nanocomposite film has slightly higher levels of hydrophilic properties when compared to pure PLA film as evidenced by contact angle measurement. This result implies that low-temperature plasma discharges can successfully improve the surface property of PLA film in a short operating time. Keywords: Low-temperature plasmas, PLA modification, Nanocomposite, Plasma modifications, Surface modifications